The effect of phonological development on reading ability - Panić Marijana; Đorđević Vivijen (Nastava i Vaspitanje, 2015)
The paper presents the results of a research obtained by examining the level of development of phonological skill and its influence on reading ability. The sample included 36 children of the second grade of regular elementary school (15 boys and 21 girls, average age: 8years and 8 months). The measuring instruments were: the Articulation Test, Repetition of Words and Logotomes Test, Phonemes Deletion Tasks, Voice Analysis Test, Voice Synthesis Test and Three-dimensional Reading Test. It was established that reading ability was not statistically significantly linked with voice articulation and voice analysis, but there was a statistically significant connection between reading ability and repetition of words and logotomes, phoneme deletion and voice synthesis. The reading ability is primarily determined by phonological skills of voice synthesis, phoneme deletion and repetition of words and logotomes. Extremely important is to develop cognitive functions and processes such as working (phonological) memory, phonological elaboration, lexical representation, auditive perception and discrimination.